Impact of Costs on Legal Risk of CHF Foreign Currency Mortgage Loans in Shaping Financial Performance of Selected Banks - Polkowska, Zofia (Journal of Finance and Financial Law, 2025)
The purpose of the article. Costs associated with legal risks, including those arising from the need to carry out loan conversions, compensate borrowers, and court or settlement costs, are an element that affects the profitability of banks that have granted such loans. The purpose of this article is to indicate the impact of costs associated with the legal risk of foreign currency mortgage loans in CHF in the context of the financial performance of selected banks in Poland. Particular attention was paid to the impact of costs related to litigation, the settlement process and loan conversions on the financial performance of banks. The article uses an analysis of studies and data published by financial safety net institutions and an analysis of the financial results of banks operating in the Polish banking sector. Due to the provisions made, banks are more prepared for the challenge of the materialization of legal risks related to foreign currency housing loans. However, it should be emphasized that this risk will be one of the main factors affecting the situation of banks in the coming years. The article complements the existing body of research on legal risk provisions with the impact of the level of provisions on the financial performance of banks operating in the Polish banking sector. Methodology. The article uses an analysis of studies and data published by financial security network institutions, as well as an analysis of the financial results of banks operating in the Polish banking sector that have the largest share of foreign currency loans in their portfolios: PKO BP S.A., Millennium S.A., Santander S.A. and mBank S.A. Results of the research. The analysis of the role of costs related to the legal risk of foreign currency mortgages in CHF in shaping the financial performance of selected banks in the Polish banking sector, indicates that this risk has a significant impact on the financial performance of the studied institutions. Due to the provisions made, banks are more prepared for the challenge of materialization of legal risk related to foreign currency housing loans. However, it should be emphasized that this risk will be one of the main factors influencing the situation of banks in the coming years. Based on the analysis, it is shown that the level of provisions made by banks related to the legal risk of foreign currency housing loans is increasing.